Kiai Pondok dan Cukong Rokok di Modjosongo: Dilema Institusi Agama dalam Ruang Kapital - Suhadi Suhadi (Antropologi Indonesia, 2009)
Kiai, alumni and santri Ilir kali first confronted with the PRD and SMID who spearheaded the various demonstrations of labor movement in East Java. Now, communism as the common enemy no longer has a clear personification and increasingly blurred. The intensity of the conflict become more intensified in mid-1998 in various areas in Java, forcing the local elites in Modjosongo do institutionalization consolidation of local leaders. Incident "communal praying" created as common platform transformation media for religion, politics and economic elite's in Madukara. When labors' demonstrations took place in Madukara several times in the transition era of the Reformation, Islamic propaganda becoming part of subjugation. This article presents how the position of the santri and the dilemma in the frame space of capital that flourished in the city.Key words: Space of capital, Santri, Labor, Cigarette brokerage